An electronic medical records review system for mobile healthcare based on web services - Yuanli Wu; Hongqiao Yang (2012 5th International Conference on Biomedical Engineering and Informatics, 2012)
With the rapid development of mobile health care, doctors have an urgent requirement to access to EMR (Electronic Medical Record) systems with iPad and other mobile tablets in wireless environment. But most existing EMR systems are based on Windows operating system, therefore how to provide mechanisms which can make EMR mobile becomes an important research issue in mobile healthcare field. This paper proposes an electronic medical review system named WSB-EMR based on web service. WSB-EMR, which aims at higher flexibility and cross-platform ability for different mobile tablet devices, uses service-oriented architecture and XML (Extensible Markup Language) technology to provide cross-platform access mode to EMR system, and can integrates HIS (Hospital Information System), EMR and LIS (Libratory Information System) systems seamlessly. Doctors can get access to patients' clinical diagnosis and treatment information at the bedside through wireless network with iPad or other tablets. Benefits are significant since the system was put into use.